1999
DOI: 10.1111/j.1439-0310.1999.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐marking and Adjacent Marking are Influenced by Sibship in Male Prairie Voles, Microtus ochrogaster

Abstract: Ferkin. M. H 1999 Over-marking and adjacent marking are influenced by sibship in male prairie voles, Microfus ochrogusfer. Ethology 105, 1-1 1. AbstractScent over-marking occurs when an animal deposits its scent mark on top of the scent mark of a conspecific. Over-marking may provide advantages in the transfer of information to the individual whose scent is on top but not to the individual whose scent is on the bottom. We tested the hypothesis that over-marking is a competitive form of olfactory communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…They found that male and female prairie voles avoid over-marking the scent marks of male conspecifics (Thomas and Kaczmarek 2002;Thomas and Wolff 2002;Wolff et al 2002). Interestingly, other studies on prairie voles, and those on meadow voles and golden hamsters indicate that they do not avoid over-marking the scent marks of same-sex and opposite-sex conspecifics (this study; Johnston et al 1997a;Ferkin 1999a;Kohli and Ferkin 1999;Johnston 2001;Ferkin et al 2004). Differences in the results between those studies and those of Thomas and co-workers may be traced to differences in methods.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…They found that male and female prairie voles avoid over-marking the scent marks of male conspecifics (Thomas and Kaczmarek 2002;Thomas and Wolff 2002;Wolff et al 2002). Interestingly, other studies on prairie voles, and those on meadow voles and golden hamsters indicate that they do not avoid over-marking the scent marks of same-sex and opposite-sex conspecifics (this study; Johnston et al 1997a;Ferkin 1999a;Kohli and Ferkin 1999;Johnston 2001;Ferkin et al 2004). Differences in the results between those studies and those of Thomas and co-workers may be traced to differences in methods.…”
Section: Discussionmentioning
confidence: 47%
“…Our data suggest that for male voles over-marking may be an incidental by-product of scent marking in areas marked by unfamiliar and unrelated male conspecifics. Interestingly, male prairie voles over-mark a greater percentage of the scent marks of unfamiliar male conspecifics than they do those of their male siblings (Kohli and Ferkin 1999). This observation suggests that male prairie voles can identify the scent marks of their brother siblings and avoid over-marking them.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Another prediction is that individuals over-mark the scent marks of same-sex competitors more than those of other same-sex conspecifics. For example, they may over-mark a greater proportion of scent marks of unfamiliar same-sex conspecifics than those of familiar siblings (Kohli and Ferkin 1999). Direct and indirect support for the competition hypothesis comes from studies on meadow voles, prairie voles, tree shrews, sifakas, golden hamsters, house mice, dogs, Mongolian gerbils, moustached tamarins, deer, bilbies, grey wolves, honey badgers, ring-tailed lemurs, bank voles, and African antelopes (Johnson and Johnson 1983;Mertl-Millhollen et al 1986;Rozenfeld et al 1987;Hurst 1990a, b;Smith and Abbott 1999;Ferkin et al 2004a;Palagi et al 2004;Lewis 2005).…”
mentioning
confidence: 99%